The mass of the Milky Way from satellite dynamics - Callingham, Thomas M.; Grand, Robert J. J.; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. We present and apply a method to infer the mass of the Milky Way (MW) by comparing the dynamics of MW satellites to those of model satellites in the